Effects of a combined protein and antioxidant supplement on recovery of muscle function and soreness following eccentric exercise. Issue 1 (3rd July 2017) - Ives, Stephen J.; Bloom, Samuel; Matias, Alexs; Morrow, Noelle; Martins, Natalya; Roh, Yookee; Ebenstein, Daniel; O'Brien, Gabriel; Escudero, Daniela; Brito, Kevin; Glickman, Leah; Connelly, Scott; et al.
Abstract: Background: An acute bout of eccentric contractions (ECC) cause muscle fiber damage, inflammation, impaired muscle function (MF) and muscle soreness (MS). Individually, protein (PRO) and antioxidant (AO) supplementation may improve some aspects of recovery from ECC, though have yet to be combined. We sought to determine if combined PRO and AO supplementation (PRO + AO) improves MS and MF following damaging ECC over PRO alone. Methods: Sixty sedentary college-aged males participated in a randomized, single–blind, parallel design study of peak isometric torque (PIMT), peak isokinetic torque (PIKT), thigh circumference (TC), and muscle soreness (MS) of knee extensor muscles measured at baseline, immediately after and 1, 2, 6, and 24 h after completion of 100 maximal ECC. Immediately, 6 h, and 22 h post-ECC, participants consumed either: carbohydrate control (CHO; n  = 14), PRO ( n  = 16), or PRO + AO ( n  = 17). Results: At baseline MS, TC, MF, macro- and micro-nutrient intakes, and total work during the ECC were not different between groups ( p  > 0.05). PIMT and PIKT (both −25%∆), TC (~1%∆) and MS (~35%∆) all changed with time ( p  < 0.05). We observed a group by time effect for PIKT (PRO + AO and PRO > CHO, p  < 0.05). At 24 h post ECC, there was a trend towards improved relative PIMT (~11%) and PIKT (~17%) for PRO + AO (~17%) and PRO (~11%) compared to CHO. An interaction indicated PRO + AO had lowest MS over time (PRO + AO > PRO & CHO, p  < 0.05). Conclusions: Our results suggest PRO facilitates recovery of muscle function within 24 h following ECC, and addition of AO ameliorates MS more than PRO or CHO alone.